The Impact of Human Resource Management Practices on Organizational Learning at Jordanian Commercial Banks - Islam Ibrahim Ahmad Zwateen; Ali Nasser Ali Al-Tahitah; Al-Baraa AbdulrahmanAl-Mekhlafi; Khaled Banyhamdan (International Journal of Scientific Research and Management (IJSRM), 2024)
Non-Indexed Publication